Comparison of different genetic testing modalities applied in paediatric patients with steroid-resistant nephrotic syndrome - Xueting Cheng; Jiahuan Chen; Xueying Yang; Han Chan; Xia Yang; Jia Jiao; Anshuo Wang; Gaofu Zhang; Xuelan Chen; Xiaoqin Li; Mo Wang; Baohui Yang; et al. (BMC, 2024)
Abstract Background Steroid-resistant nephrotic syndrome (SRNS) are monogenic in some cases, however, there are still no clear guidelines on genetic testing in the clinical practice of SRNS in children. Methods Three hundred thirty-two children were diagnosed with SRNS, and all children underwent genetic testing, including gene panels and/or whole-exome/genome sequencing (WES/WGS), during treatment. We analysed the relationship between clinical manifestation and genotype, and compared different genetic testing methods' detection rates and prices. Results In this study, 30.12% (100/332) of children diagnosed with SRNS had monogenic causes of the disease. With 33.7% (122/332) of children achieving complete remission, 88.5% (108/122) received steroids combined with tacrolimus (TAC). In detectability, WES increased by 8.69% (4/46) on gene panel testing, while WGS increased by 4.27% (5/117) on WES, and WES was approximately 1/7 of the price of WGS for every further 1% increase in pathogenicity. Conclusions We verified that steroids combined with TAC were the most effective option in paediatric SRNS. In detection efficiency, we found that WGS was the highest, followed by WES. The panel was the lowest, but the most cost-effective method when considering the economic-benefit ratio, and thus it should be recommended first in SRNS.